RANCANG BANGUN SISTEM PEMESANAN MAKANAN/MINUMAN BERBASIS PHP (Information Technology and Telematics, 2013)
Due to the advanced technology and the developing world, creation of a system that is made according to the specifications and needs both in day-to-day and the world of work. Food and drink ordering system is needed in order to provide ease and convenience for the customer and the restaurant. The authors designed a system of ordering food and beverages with the intent and purpose to make a better quality of service and efficiency. The system is built using PHP programming language and MySQL database. The result of this system, customers can place an order through a system that has been available on the computer. Once consumers order, the order will be immediately accepted by the chef for further processing. Orders will be delivered to consumers. To make a payment transaction, consumers can contact the cashier, the cashier will be able to process payment transactions in accordance with the results of customer orders. Keywords: Booking System food drink, ordering menu, ordering